Penyuluhan Pendidikan Karakter dalam Meningkatkan Kinerja Remaja Masjid Al-Ikhlas Lingkungan Kampung Baru - Jumaisa; Nurfitriani (Jurnal Makkareso, 2023)
The youth management of the Al-Ikhlas Mosque in the Kampung Baru neighborhood consists of 17 people who have minimal understanding regarding how character education should be able to build their personal morals in the future and can be applied to everyday life, especially in carrying out their duties and responsibilities as mosque administrators. This PKM was carried out to provide knowledge and understanding regarding character education in improving performance carried out at the Al-Ikhlas mosque in the Kampung Baru environment. The implementation method is the interview stage with the youth leader, taking care of the administration and infrastructure for the activity. The implementation stage is conducting character education outreach as an effort to improve the performance of mosque youth administrators. The evaluation stage is evaluating the activity process, the smoothness of the activity, member participation, and the obstacles faced. The results showed that participant attendance during the activity was 95%, participants had enthusiasm and curiosity about the outreach activities being held, while activities such as attention and questions and answers were around 90%. The role of Al-Ikhlas Mosque teenagers in forming the religious character of teenagers is quite good in realizing activity programs as a form of management performance.